Macroeconomics and Famine. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
The aim of the paper is to shift the focus of famine analysis away from food supply towards the macroeconomic determinants of food entitlement-i.e., to the ability of individuals to purchase food. Towards this end, we develop a model to demonstrate how loose monetary and fiscal policies may give rise to famine even when there is no change in per capita food output. We illustrate our findings with a description of the 1974 Bangladesh famine.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet